THE GENDER IMPACT OF FISCAL CAPACITY AND PUBLIC SPENDING: AN INTER-PROVINCIAL STUDY OF LOCAL GOVERNMENTS IN INDONESIA - Sandhyakalaning Jiwatami Ridwan Putri; Nurhidayati; Brama Yudha Kusmara (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
This study investigates the relationship between local fiscal capacity, public sector expenditure, gender equality, and economic inclusion across districts and cities in West Java, Central Java, and East Java from 2015 to 2024. Using a panel dataset combining gender indicators (IPG, IDG), inclusive economic development (IPEI), and fiscal variables (PAD, DAK, and sectoral expenditures), the analysis relies exclusively on correlation-based evidence to explore the structural linkages within the fiscal–gender–inclusion nexus. The results reveal that PAD is positively correlated with education, health, and economic spending, while DAK exhibits a compensatory negative correlation with most development indicators, consistent with its allocation to more disadvantaged regions. Sectoral spending shows divergent patterns: health expenditure correlates positively with gender development (IPG), education spending shows a small negative relationship due to targeting of lagging areas, and economic spending demonstrates weak gender-related linkages. Both IPG and IDG are positively associated with IPEI, indicating that regions achieving higher gender equality also experience more inclusive economic outcomes. Overall, the findings support theoretical expectations that fiscal capacity and public spending shape gender and inclusion outcomes, but also highlight substantial provincial disparities in fiscal effectiveness. The study underscores the need for gender-responsive and regionally targeted fiscal strategies to promote inclusive development.